Thiopurine methyltransferase and thiopurine metabolite testing in patients with inflammatory bowel disease who are taking thiopurine drugs. (July 2009) - Sheffield, Leslie J; Irving, Peter; Gupta, Arun; Byron, Keith; Macrae, Finlay A; Phillimore, Hazel; Dronavalli, Mithilesh; Rose, Rosemary; George, Peter; Walmsley, Trevor; Dixon, Barbara; Poole, Susan; et al.
Thiopurine methyltransferase genotyping and thiopurine metabolite testing has been established as an adjunct to monitoring patients taking thiopurine drugs. This special report describes the clinical implications for this type of testing for patients with inflammatory bowel disease who are taking thiopurine drugs. A total of 10% of patients were found to be intermediate metabolizers and the mean dosage (in mg/kg equivalent) was lower in intermediate metabolizers than extensive metabolizers. The metabolite levels did not correlate with scores measuring clinical severity but levels of 6-methylmercaptopurine were related to the dosage of the drugs. Despite considerable study of thiopurine methyltransferase testing in the literature, it is still not widely used in many geographical areas. This study adds to the evidence about using such testing as well as expanding the role of simultaneously measuring thiopurine metabolites. Further work is planned to evaluate the uptake when such testing becomes available locally as a clinical service.